Pemanfaatan Perpustakaan Digital (E-Library) Sebagai Salah Satu Strategi Peningkatan Kualitas Pendidikan dan Penelitian di Perguruan Tinggi - Himawan, Himawan; Kusuma Wardani, Deyana; Kartika Kusuma Winahyu, Raden Rara (Faktor Exacta, 2024)
The university plays an important role in educating the future generations of the country. One of the universities efforts is to use the facilities and infrastructure in their respective universities to achieve this goal. Astra Polytechnic is one of the higher education institutions in the Cikarang region with unsuitable infrastructure to improve the quality of university services and research activities for all academic communities at the Astra Polytechnic Campus. The infrastructure is the campus library that is still operated in traditional ways, which certainly does not meet the information needs of the digitalization era, which requires the management and delivery of up-to-date and accurate information. Consequently, the Astra University Research and Community Service Institute (LP2M) and the Information Management Study Programme collaborated to establish digital libraries to improve the quality of university services for the entire Astra University College community. In addition, libraries must change (transformation) in order to survive today's digitalization. Ultimately, the use of library information systems is expected to help librarians and library staff manage library collections, memberships and all transactions, so that librarians have more time to do other things and be more efficient in terms of time management.